BRECHTIAN STYLE OF RESISTANCE IN HERTA MÜLLERS NOVEL HERZTIER - Wisma Kurniawati (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2019)
Herta Müller is a Romanian-born author who is currently internationally known for his resistance novels. She was deported by the Romanian ruler led by president Ceausescu as she was considered endangering the Romanian government. In her escape, Müller created a novel depicting the resistance to injustice perpetrated by the Romanian authorities, who practiced a cruel proletarian dictatorial system of government. Herztier is the most concrete novel that shows her resistance to the authorities. According to Ashcroft, Griffiths, and Tiffin, resistance literature is closely related to context, and Said said that the situation and condition of context, determine the characteristics of resistance in the novel. The forms of resistance carried out by the characters in the Herztier novel, show similarities to the resistance style of the characters created by the German playwright Bertold Brecht, resistance that tends to be individual and clandestine, or what Scott calls the Brechtian style of resistance . Based on this background, this study is intended to describe (1) the characteristics of popular resistance styles of the protagonists in the Herztier novel; (2) situations and conditions that influence the resistance styles of the characters in the Herztier novel. The results of the study show that (1) the characters in the Herztier novel take the fight against the authorities individually and are not organized by being stubborn but passive, pretending to obey, pretending not to know, stealing, or fleeing abroad; (2) the resistance is caused by weak humans under the oppression of authoritarian and cruel rulers. The results of this study are expected to foster public awareness of reality, and in the next stage move them to actively participate in the struggle to create a just society.